T372R Mutation Status in Yin Yang 1 Gene in Insulinoma Patients - Irshad, Khushboo; Jyotsna, Viveka P.; Agarwal, Shipra; Chosdol, Kunzang; Pal, Sujoy; Deepak, Rakesh Kumar (Hormone and Metabolic Research, 2017)
Insulinomas are rare pancreatic neuroendocrine tumors. The genetic causes underlying insulinoma are still being investigated. Recently, 3 independent studies reported a recurrent somatic mutation in YY1 gene (C>G; Thr372Arg) among insulinoma patients belonging to Chinese and Western Caucasian populations, which was found to increase insulin secretion by β-cells. However, the status of this key gene variation remains unknown in patients of other ethnicities. We, therefore, screened Indian sporadic insulinoma patients for YY1 T372R mutation in the present study. Seventeen patients diagnosed with insulinoma were recruited retrospectively and their records of family history and clinical parameters were collected. Formalin-fixed paraffin-embedded tumor tissues were used to extract genomic DNA, which was subjected to PCR amplification of YY1 exon 5, followed by Sanger sequencing. Nucleotide sequences thus obtained were aligned against the documented sequence of YY1 exon 5. We found absence of C to G mutation at YY1 codon 372 in all 17 (100%) insulinoma tissues analyzed. On comparison with the mutation frequency observed in the Chinese patients, our results point to genetic heterogeneity in the pathogenesis of insulinoma. This is the first report on the status of YY1 T372R in insulinoma cases of Indian origin. This also warrants analysis of other documented as well as novel mutations in genes in insulinoma tumorigenesis.
Keywords: YY1 T372R mutation; pancreatic neuroendocrine tumor; insulinoma